Screening landraces for additional sources of field resistance to Cassava Mosaic Disease and green mite for integration into the Cassava Improvement Program - Raji, A.; Ladeinde, O.; Dixon, A. (Wiley, 2008)
Twelve cassava landraces were evaluated for sources of resistance genes to diseases and pests of major economic importance in Africa. The objective was to assess their levels of field resistance to mosaic disease (ACMD), bacterial blight (CBB), anthracnose (CAD), and green mite (CGM), compared to TMS30572, an elite cultivar widely adopted in Africa. Considerable genotypic variation was observed among cultivars for resistance to ACMD and CGM but not for CBB and CAD. The lowest mean incidence of 12% and severity of 1.8 on a scale of 1–5 for ACMD was recorded for Atu, a landrace with farmer acceptable qualities. In comparison, the improved cultivar, TMS 30572, had a mean disease incidence of 72% and a severity score of 2.8. Another landrace, MS-20 had the lowest CGM damage score (2.1) while TMS 30572 emerged as one of the susceptible cultivars with a damage score of 3. Additional sources of resistance to ACMD and CGM that may possibly be better than the popular improved cultivar, TMS 30572, were identified in this study. These could serve as novel sources of additional genes to complement existing resources for elite cassava breeding in Africa.